The Correlation between Hematological Profiles with Types of Febrile Seizures in Children at RSUD dr. Adhyatma, MPH Semarang - Prayoga, Rizka Margiana; Ramaningrum, Galuh; Ratnaningrum, Kanti; Prihandani, Oky Rahma (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2025)
Seizures known as febrile seizures occur in children between the ages of six months and five years when they have an increase in body temperature (any temperature above 38 degrees Celsius), which is not brought on by an intracranial process. The research aims to determine the correlation between hematological profile, temperature, and nutritional status with the type of children’s febrile seizure at RSUD dr. Adhyatma, MPH Semarang. This study used an analytical observational method with a cross-sectional approach and total sampling technique. Accordingly, medical records at RSUD dr. Adhyatma MPH Semarang became the source of data in this study. Moreover, analysis of the study’s data utilized the Chi-square test. Based on bivariate analysis, it was found that a p-value of 0.511 between temperature and type of febrile seizure, a p-value of 0.624 between nutritional status and type of febrile seizure, a p-value of 0.100 between hemoglobin levels and type of febrile seizure, and p-value of 0.026 number of leukocytes was related to the type of febrile seizure. There is a relationship between the number of leukocytes and the type of febrile seizure.